Analysis of miRNAs miR-125a-5p, -27a-5p, -193a-5p, -135b-5p, -451a, -495-3p and -136-5p in parental ovarian cancer cells and secreted extracellular vesicles - G. O. Skryabin; A. A. Beliaeva; A. D. Enikeev; D. V. Bagrov; A. M. Keremet; А. V. Komelkov; D. S. Elkin; D. M. Sylantieva; E. M. Tchevkina (Успехи молекулярной онкологии, 2024)
Introduction. The identification of markers for liquid diagnostics of ovarian cancer is one of the most urgent tasks of gynecologic oncology. Currently, extracellular vesicles (EVs) are of great interest as a source of oncomarkers, including miRNA markers. We have previously shown that the levels of miR-125a-5p, -27a-5p, -193a-5p and 135b-5p are significantly elevated and miR-451a, -495-3p and -136-5p are significantly decreased in the EVs from uterine aspirates of ovarian cancer patients.Aim. Analysis of miR-125a-5p, -27a-5p, -193a-5p, 135b-5p, 451a, 495-3p and -136-5p levels in ovarian cancer cell cultures and secreted EVs.Material and methods. Cultivation of ovarian cancer cell lines: OVCAR-3, OVCAR-4, OVCAR-8 and SKOV3; EVs isolation from conditioned medium by ultracentrifugation; EVs validation by nanoparticle tracking analysis (NTA), transmission electron microscopy (TEM), western blot analysis of exosomal markers; isolation of miRNAs from cells and EVs; analysis of miRNAs by Stem-Loop – reverse transcription-quantitative polymerase chain reaction.Results. In all cell lines studied, the expression of miR-125a-5p, -27a-5p, -193a-5p and -135b-5p significantly exceeds the expression of -451a, -495-3p and -136-5p. All ovarian cancer cell lines are featured by a “cells >EVs” ratio for highly expressed miRNAs and “EVs >cells” ratio for poorly expressed miRNAs.Conclusion. The results of the study support the relation between the differential expression of studied miRNAs and the pathogenesis of ovarian cancer and confirm the high diagnostic potential of these molecules.